2017
DOI: 10.1016/j.ajhg.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale trans -eQTLs Affect Hundreds of Transcripts and Mediate Patterns of Transcriptional Co-regulation

Abstract: Efforts to decipher the causal relationships between differences in gene regulation and corresponding differences in phenotype have been stymied by several basic technical challenges. Although detecting local, cis-eQTLs is now routine, trans-eQTLs, which are distant from the genes of origin, are far more difficult to find because millions of SNPs must currently be compared to thousands of transcripts. Here, we demonstrate an alternative approach: we looked for SNPs associated with the expression of many genes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 48 publications
1
83
0
Order By: Relevance
“…Furthermore, variants far from the transcriptional start site (TSS) of a gene, trans-eQTL, explain more of the heritability of T2D than those near the gene, cis-eQTL, and there is mounting evidence for the importance of these variants in a variety of phenotypes (9)(10)(11). That trans-eQTL, which can influence hundreds of genes in humans (12), might have an impact on the phenotype is consistent with similar observations in model organisms (13). However, large-scale detection of trans-eQTL across populations and tissues (14) has only recently become feasible in humans, and our understanding of how multiple cis-and trans-eQTL influence gene expression and cellular functions in different tissues is incomplete.…”
mentioning
confidence: 99%
“…Furthermore, variants far from the transcriptional start site (TSS) of a gene, trans-eQTL, explain more of the heritability of T2D than those near the gene, cis-eQTL, and there is mounting evidence for the importance of these variants in a variety of phenotypes (9)(10)(11). That trans-eQTL, which can influence hundreds of genes in humans (12), might have an impact on the phenotype is consistent with similar observations in model organisms (13). However, large-scale detection of trans-eQTL across populations and tissues (14) has only recently become feasible in humans, and our understanding of how multiple cis-and trans-eQTL influence gene expression and cellular functions in different tissues is incomplete.…”
mentioning
confidence: 99%
“…Based on the PhenoScanner database, we found that rs10830963 appeared to affect the expression levels of distant genes. Emerging evidence suggests that some SNPs affect the expression of distant genes and genes residing on other chromosomes (trans‐eQTLs) . Thus, it is biologically plausible that rs10830963 may affect the expression of genes and be involved in the pathogenesis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that some SNPs affect the expression of distant genes and genes residing on other chromosomes (trans-eQTLs). 30,31 Thus, it is biologically plausible that rs10830963 may affect the expression of genes and be involved in the pathogenesis of GDM. However, functional studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…New methods are developed to integrate multiple molecular phenotypes. 29,72,91,147 Human quantitative genetics is thus leaping into the area of systems biology. 148…”
Section: Caution and Limitations In Using Molqtlsmentioning
confidence: 99%